Impact of Collaborative Technology on Work Performance: A Study of IT Women Rejoining Post Maternity Leave (Prithvi Academic Journal, 2026)
This research examined the impact of Collaborative Technology (CT) its precursors (Access to Networks and Mentorship (ANM), Social Support (SS), and Work–Family Balance (WFB)) on organisational culture, organisational effectiveness, and work performance. This study focused on women employees in IT sector in Karnataka who have recently rejoined to work after their maternity leave. It employed a quantitative approach and collected data from, 395 respondents using survey. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to simultaneously assess the measurement and structural aspects of the model. Convergent and discriminant validity analysis confirmed that the indicators of ANM, SS, WFB, CT, OC and OE and WP were reliable in measuring their corresponding constructs and discriminating their respective constructs. The structural model evaluated the relationship between ANM, SS, WFB and CT and further to OC, OE and WP. The strength of these relationships was measured by effect size (f 2) and IPMA determined the relative importance and performance of constructs with OE, OC and CT being identified as major drivers of WP. The results of the study demonstrate the value of integrating technology with supportive organisational resources to promote efficient and seamless collaborative work processes and unambiguous communication. This study is useful for organisations aiming to improve technology adoption in a manner that supports organisational culture and performance outcomes. It also provides a foundation for further research on the long-term and cross-cultural impacts of collaborative technology across diverse industries and settings.